An Analysis of Digital Literacy Level in Technical Aspects Among Fresh Graduates of Early Childhood Educators - Fadilah, Siti Nur (Journal of Early Childhood Education (JECE), 2024)
This research aims to analyze the level of digital literacy among fresh graduates of early childhood educators, with a special focus on technical aspects. Through a survey, this research illustrates the readiness of fresh graduates to face technology needs in the early childhood education environment. The research results show that the majority of fresh graduates still need to develop digital literacy skills, especially in technical contexts. Despite having a basic formal education, several respondents face difficulties in integrating technology into early childhood learning activities. The implications of the results of this research show the importance of expanding learning approaches that provide support for digital literacy, in line with the efforts of education administrators and higher education institutions to ensure that new graduates in the early childhood education have sufficient skills to overcome the challenges of digital world of education.